2013
DOI: 10.1093/carcin/bgt331
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 axis promotes directional migration of colorectal cancer cells through upregulation of integrin αvβ6

Abstract: Colorectal cancer (CRC) displays a predilection for metastasis to liver. Although stromal cell-derived factor-1 (SDF-1)/CXCR4 plays an important role in the liver metastasis, the molecular mechanism still remains obscure. We previously reported that integrin αvβ6 was implicated in the progression of CRC. However, no data are currently available on the cross talk between CXCR4 and αvβ6. In the present study, we first demonstrated the cross talk between CXCR4 and αvβ6 and their role in liver metastasis of CRC. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 46 publications
5
66
0
Order By: Relevance
“…In ovarian cancer, SDF-1 has recently been shown to upregulate the Integrin molecules ß1 and ß3 and to promote invasion by the SDF-1-specific C-X-C chemokine receptor type 4 (CXCR4) axis [162]. In colorectal cancer, αvß6 Integrin was shown to effect the same kind of upregulation [163]. These findings may be of clinical relevance, as CXCR4, often expressed and detected in cancers, is found only at low or non-detectable levels in healthy tissues [164].…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%
“…In ovarian cancer, SDF-1 has recently been shown to upregulate the Integrin molecules ß1 and ß3 and to promote invasion by the SDF-1-specific C-X-C chemokine receptor type 4 (CXCR4) axis [162]. In colorectal cancer, αvß6 Integrin was shown to effect the same kind of upregulation [163]. These findings may be of clinical relevance, as CXCR4, often expressed and detected in cancers, is found only at low or non-detectable levels in healthy tissues [164].…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%
“…1 Stromal cell-derived factor (SDF)-1α is cognate ligand of CXCR4 and high levels expression of SDF1α /CXCR4 axis is associated with lung, liver and lymph nodes metastasis. 2 SDF1α /CXCR4 axis plays key role in human development, including organogenesis, vascularisation, haematopoiesis, and embryogenesis. 3 More recent evidence shows that the SDF-1α /CXCR4 axis acts as key regulator of metastasis in leukemia & several solid tumors and also plays an important role in self renewal, differentiation potential, cell adhesion, tumorigenicity & tumor vascularization capacity of tumor cell.…”
Section: Introductionmentioning
confidence: 99%
“…28 In order to detect the influence of LPS to SDF-1a/CXCR4 axis, the expression of SDF-1a and CXCR4 was determined. We found that SDF-1a expression was significantly increased in the liver of LPSchallenged BABL/c mice ( Fig.…”
Section: Lps Contributed To Hepatic Metastasis Of Colon Cancer Cellsmentioning
confidence: 99%